NEURO DEVELOPMENTAL CONSEQUENCES OF NEONATAL HYPOGLYCEMIA - Orhideja Stomnaroska; Valentina Dukovska; Dragan Danilovski (Macedonian Academy of Sciences and Arts / Sciendo, 2020)
Neonatal hypoglycemia (HG) can cause neurologic damage, epilepsy, mental retardation, behavioral and personality disorders and death. The longest the HG lasts and the greatest the glucose nadir the consequences are more pronounced. Comorbidities are rather important in development of neurological damage. Hypoxemia and ischemia can cause permanent brain damage. Small for gestational age (SGA), large for gestational age (LGA), intrauterine growth restriction, gestational age bellow the 37th week, low Apgar score, sepsis, children whose mothers have toxemia, diabetes or chorioamnionitis are all newborns with increased HG risk. Comparing 34 patients with NH and 34 children without NH with similar GA, BW, BL, the Apgar score, we found statistically significant differences in motor and mental development using the Griffith scale. Children with neonatal HG fared significantly worse than those without neonatal HG. Therefore, CBG measurements and early recognition of neonatal HG is of significant importance in preventing motor and mental damage in children. A larger and well-balanced cohort of patients followed for a longer period is also necessary to clarify and discern in detail the importance of neonatal HG and other perinatal factors in neurodevelopmental damage.
Keywords: neonatal hypoglycemia; neurodevelopmental damage; Griffith scale